PENERAPAN METODE ASOSIASI DENGAN ALGORITMA APRIORI UNTUK MENDUKUNG STRATEGI PROMOSI - Rizky Kurniawan; Ridwan Yusuf (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Business management in a building shop business is one way that can help business activities to get the best sales results. In business management, several strategies are needed, for example, the strategy of selling a collection of building goods into one type of product category, using this strategy buyers who usually only buy one item of goods can buy several items at once. This can increase sales patterns in the building shop. Therefore, the author uses one method, namely the association method with the a priori algorithm to find patterns in a building goods sales transaction every year, so that later the frequency of itemsets is found based on several determinant items, support and confidence values, to determine the association between combinations of product items. From the results, it will be used as a promotional media at Prima Jaya Baja Store so that it can support the level of sales of building goods products and can soon grow rapidly and become one of the reference stores for the sale of building goods in Central Lampung in particular and Lampung Province in general.